Estimation of Impact Strength of Kevlar/Basalt and Kevlar/Glass Interwoven Composite Laminate after High-Velocity Bullet Impact - J. Jensin Joshua; Dalbir Singh; Y. Murali Krishna; P. Sivaprakasam; D. Raja Joseph; P. S. Venkatanarayanan (Advances in Materials Science and Engineering)
The application of composite materials has increased so drastically in the aerospace industry. The Impact strength signifies the importance of composite materials when exposed to suddenly applied loads. This paper is focused on describing the behavior of interwoven kevlar/glass-epoxy and kevlar/basalt-epoxy composite laminate under high-velocity bullet impact. The composite lamina of kevlar/glass and that of kevlar/basalt are prepared using three different weaving techniques. The composite laminates are prepared using the compression moulding technique. The laminates have been subjected to high-velocity bullet impact. The velocity range is from 220 m/s to 260 m/s. The impact damage area in the laminate has been assessed through ultrasonic pulse echo submerged nondestructive technique. The impact strength has been calculated using the damaged area derived using the impact energy absorbed by the laminate. The results have shown that the maximum impact which found out to be kevlar/basalt (KB 1 × 1) is 28.24 J/cm2.